Exploring the Scope of Theater of the Oppressed in Medical Education - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Nandkishor J Bankar (Wolters Kluwer Medknow Publications, 2024)
Theater of the oppressed has been regarded as a dynamic tool to bring about social change and empowerment of the audience. This theatrical exposure to medical students plays a significant role in the delivery of comprehensive training to medical students, which is not only restricted to clinical knowledge but extends to cultural and interpersonal skills to ensure the delivery of comprehensive patient care. In conclusion, the theater of the oppressed has the potential to prepare empathetic and compassionate medical practitioners. To augment the quality of healthcare delivery, this kind of exposure can help medical students in bridging the gap between theory and clinical practice.